Postmyocarditis Ventricular Tachycardia in Patients with Epicardial‐Only Scar: A Specific Entity Requiring a Specific Approach. (5th November 2014) - BERTE, BENJAMIN; SACHER, FREDERIC; COCHET, HUBERT; MAHIDA, SAAGAR; YAMASHITA, SEIGO; LIM, HAN; DENIS, ARNAUD; DERVAL, NICOLAS; HOCINI, MÉLÈZE; HAÏSSAGUERRE, MICHEL; JAÏS, PIERRE
Epicardial‐Only VT Ablation Background Nonischemic cardiomyopathy is a heterogeneous condition providing a favorable substrate for ventricular tachycardia (VT). Objective The purpose of this study is to further characterize the substrate in a subset of postmyocarditis patients with epicardial‐only scar. Methods Twelve postmyocarditis patients (11 male, 49 ± 14 years, left ventricular ejection fraction 49 ± 12%) with VT and epicardial‐only scar were included for analysis comparing automatic high‐amplitude normal activity (HANA) maps to manually adjusted maps of based on local abnormal ventricular activity (LAVA) electrograms when present. A combined endocardial (endo) and epicardial (epi) approach was used in 11/12 with usual bipolar/unipolar voltage thresholds and analyzed using image integration. Results A delayed enhancement MRI scar area of 52 cm2 (38, 59) and multidetector CT wall thinning area of 18 cm2 (14, 35) was found. Bipolar voltage substrate mapping (160 points [101, 239] endo, 553 points [232, 713] epi and LAVA were found only epicardially [443 LAVA points] in all) illustrated a low‐voltage area of HANA: 1 cm2 (0, 10) endo, 25 cm2 (22, 39) epi and LAVA: 1 cm2 (0, 10) endo, 39 cm2 (28, 51) epi. Manual maps performed better than automatic maps for delineating low‐voltage area with a higher overlap with scar area on delayed enhancement magnetic resonance imaging (DE‐MRI; 76% [66, 94] vs. 45% [35, 62]; P = 0.04). In addition, manual voltage maps also showed a higher overlap with location of LAVA (LAVA in normal voltage area: 3% [0, 9] vs. 35% [32, 41]; P < 0.05). Conclusion In postmyocarditis patients with epicardial‐only scar, automatic voltage mapping may miss or minimize the electrical VT substrate. DE‐MRI and manual LAVA‐based voltage mapping are necessary to optimize scar delineation. Epicardial access is critical for mapping and ablation in this condition.